Fuzzy Delphi Method Application In The Development Of I-Aqran Module For Arabic Vocabulary Consolidation - Yusof, Nabihah; Baharudin, Harun; Hamzah, Mohd Isa; Abdul Malek, Nur Izzah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The development of digital systems in learning is gaining attention at, significantly higher education level. Through the digital world, technological innovation makes social life and everyday lifestyle more accessible than ever before. The use of technology has a positive impact on lifestyle and has a positive impact on education. This study aims to obtain experts’ consensus on the appropriate and accurate elements to be included in the I-Aqran module as an approach to Arabic vocabulary consolidation in the learning of UiTM students. This study uses the Fuzzy Delphi Method (FDM), in which experts’ views and consensus on the six primary constructs containing 34 tested items are produced. Fifteen (15) experts were selected from seven (7) educational institutions in Malaysia as a study sample. The findings show that these experts arrived at a consensus on 27 tested items in which they have a mean score and experts’ evaluation of less than the threshold value(d) ≤ 0.2. The percentage of these experts’ consensus also shows that 27 items tested are above the value of 75%, while seven remaining tested items prove otherwise and therefore rejected. All items that gained experts’ consensus are then listed down in tables based on sequence ranking and its relation from least important to most important items. This study can benefit not only lecturers and students for Arabic vocabulary consolidation but also the developer of learning modules in transforming education through collaboration with interactive technology.